Backlash Politics of Sustainable Development Goals in the Brazilian Context - Marcela Donini de Lemos (Revue Internationale des Études du Développement)
There are currently several challenges related to climate change linked to production and consumption methods. In response, the Sustainable Development Goals were created in 2015, with social and environmental factors, not just economic ones. However, there are groups that act as institutional activists with backlash policies. This article aims to analyze actors in the Brazilian executive and legislative branches related to far-right parties who are working to block these changes. Exploratory research was used to identify the actors and analyze their discourses. As a final consideration, far-right institutional activists have acted against the 2030 Agenda and its guidelines, by using discourses to maintain their privileges, linked to past development.